The Impact of Intradialytic Pedaling Exercise on Arterial Stiffness: A Pilot Randomized Controlled Trial in a Hemodialysis Population. (6th November 2017) - Cooke, Alexandra B; Ta, Vincent; Iqbal, Sameena; Gomez, Yessica-Haydee; Mavrakanas, Thomas; Barré, Paul; Vasilevsky, Murray; Rahme, Elham; Daskalopoulou, Stella S
Abstract: OBJECTIVES: Regular exercise is known to reduce arterial stiffness (AS) in hemodialysis patients. However, the impact of a more realistic intradialytic form of exercise, such as pedaling, is unclear. We aimed to examine (i) the effect of intradialytic pedaling exercise on AS over 4 months and (ii) the longer term effect of pedaling on AS 4 months after exercise cessation. METHODS: Patients on stable in-center hemodialysis (3 x/week) were randomly assigned 1:1 to either intradialytic pedaling exercise (EX) or to a control group receiving usual hemodialysis (nonEX) for 4 months. At baseline and 4 months, peripheral and central blood pressure (BP) indices, heart rate (HR), augmentation index HR corrected (AIx75), and carotid-femoral pulse wave velocity (cfPWV) were assessed (applanation tonometry). Measurements were repeated in the EX group 4 months postexercise cessation. RESULTS: As per protocol analysis was completed in 10 EX group participants (58 ± 17 years, body mass index 26 ± 4 kg/m 2 ) and 10 nonEX group participants (53 ± 15 years, body mass index 27 ± 6 kg/m 2 ). Peripheral and central BP was unchanged in both groups. AIx75 was unchanged in the EX group, however, a significant median increase of 3.5% [interquartile range, IQR 1.0, 8.5] was noted in the nonEX group ( P = 0.009). We noted a significantly greater absolute decrease in cfPWV in the EX group compared to controls: −1.00 [IQR −1.95, 0.05] vs. 0.20 [IQR −0.10, 0.90] ( P = 0.033). Interestingly, the decrease in cfPWV observed in the EX group was partially reversed 4 months after exercise cessation. CONCLUSION: Intradialytic pedaling exercise has a beneficial impact on AS. This relationship warrants further investigation. CLINICAL TRIALS REGISTRATION: Trial Number #NCT03027778 (clinicaltrials.gov )